THE EFFECTS OF PERSONALITY CHARACTERISTICS ON TIME MANAGEMENT SKILLS: RESEARCH ON VOCATIONAL SCHOOL STUDENTS - Musa Karaçor; Ozan Çatır; Kenan Sakallı (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Time management has great prospects for individuals toachieve success in both their education, social and professional lives. Inaddition, personality traits that individuals possess are also leading tosuccess. Personality traits of the undergraduate students and their perspectiveon the concept of time management will contribute to their rapid progress incareer life both in their educational life and after their graduation. Thepurpose of this study is to determine the effect of personality traits on thetime management skills of vocational college students. Descriptive surveymethod was preferred in this study, the questionnaire was used to obtain thedata. Sampling as a method of easy sampling method is random sampling method isselected. The study was conducted on 420 students studying in vocationalschools. The obtained data were analyzed (in the SPSS package program Frequency, Percentage, Mean, Reliability,Validity, Correlation, Regression). As a result of the study, personalitytraits were found to be effective on time management skills.